Manufacturing Memories and Directing Dreams: Commemoration, Community, and the Closing of Maple Leaf Gardens - Field, Russell (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
In February 1999, the Toronto Maple Leafs moved from Maple Leaf Gardens (MLG) to a modern new arena, Air Canada Centre (ACC), events that were telecast live in conjunction with Hockey Night in Canada. These were produced shows intended to highlight certain narratives, communicate certain messages, and select for viewing certain elements. An analysis of them reveals important meanings in the confluence of sport, place, and representation, as well as iconographic messages about Canadian identity. In commemorating one arena and inaugurating another, these telecasts operationalized a "discourse of tradition," which produced subjects who shared the preferred memories of MLG that were being celebrated and transferred to ACC.